NEW FORMULAR FOR APPROXIMATE SOLUTIONS OF THE LINEAR DIFFERENTIAL EQUATIONS OF THE II AND III ORDER - Kujumdžieva-Nikoloska, Marija; Dimitrovski, Dragan (Matematichki Bilten, 1993)
In this paper is used a simple quadrature process for approximate solution of a linear differential equations of II and III order with analytical coefficients.